Low-frequency dynamics of an electrorheological fluid in squeeze and shear mode. Part I: experiments. (April 2015) - Norrick, N; Dohnal, F; Bauer, J
Electrorheological fluids (ERFs) offer a rapid control of damping using very low power requirements. Different models have been proposed to simulate the hysteresis phenomenon observed experimentally in ERF. This paper describes the steps to be taken to extract measurements of an ERF in squeeze and shear mode. A novel modular test facility was designed to perform measurements of a specific ERF in squeeze and shear mode. This device allows the measurement of the dynamic response of the fluid under various excitation conditions. Dense measurement grids of fluid force and electrode displacement at harmonic excitation are collected in dependency of the excitation frequency, the displacement amplitude and the applied electric field. The main problems to be solved during the setup and execution of the measurements are discussed. The steps to be taken during signal processing to achieve high-quality measurements as inputs for material model fitting are described in detail. Example measurements for both squeeze and shear mode are presented. The fitting of the obtained results to a material model for ERF and discussion of the resulting extended Bouc–Wen model will be the topic of an accompanying paper.